Galvenie ģimenes uzņēmumu efektīvas pārmantošanas faktori – pārmantotāju viedoklis - Baur, Markus (Latvijas Universitāte, 2016)
In search of success factors that might support the effectiveness of succession in family businesses this study has shed light on the perspective of the successor. Based on the framework of systems theory and following a sequential exploratory research strategy, problem-centered interviews with 13 effective cases of family businesses have been conducted and an online-survey with 65 respondents has been used to evaluate the findings. In the sense of triangulation, the findings further have been assessed and strengthened by an expert round. As a result, this work provides insights on diverse complex succession cases, offers a variety of conclusions for the managerial practice on the basis of 14 key factors and summarizes the findings in an innovative management model for effective succession. Key words: effective succession, family business
Key factors for effective succession in the family business - the successor's view
Elektroniskā versija nesatur pielikumus
Keywords: Vadībzinātne [angļu val.]; Vadībzinātne; Vadība, administrēšana un nekustamo īpašumu pārvaldība